ANALYTICAL EXPOSITION TEXT-SHEET FOR COLLEGE STUDENTS IN READING COMPREHENSION - Dharma, Yokie Prasetya; Meo, Ferdinanda Itu (STKIP Persada Khatulistiwa Sintang, 2024)
The research specifically examines the analytical exposition text sheets to improve reading comprehension among third-semester English education students. By using classroom action research, the study follows a cyclic process of planning, acting, observing, and reflecting. Participants selected from a specific class undergo assessments through observation sheets, field notes, and reading comprehension tasks. The findings indicate that using analytical exposure text sheets significantly enhances students' reading comprehension, as evidenced by a notable increase in average grades. These text sheets, characterized by a clear structure for presenting arguments, logical reasoning, and supporting evidence, prove effective in fostering critical thinking skills. The success of this method underscores its potential as a valuable tool for educators, offering a structured yet flexible approach that accommodates diverse learning styles.